Enhanced Collective Magnetic Properties Induced by the Controlled Assembly of Iron Oxide Nanoparticles in Chains. (11th February 2016) - Toulemon, Delphine; Rastei, Mircea V.; Schmool, David; Garitaonandia, José Sáiz; Lezama, Luis; Cattoën, Xavier; Bégin‐Colin, Sylvie; Pichon, Benoit P.
Abstract : 1D assemblies of magnetic nanoparticles are of great potential for designing novel nanostructured materials with enhanced collective magnetic properties. In that challenging context, a new assembly strategy is presented to prepare chains of magnetic nanoparticles that are well‐defined in structure and in spatial arrangement. The 1D assembly of iron oxide nanoparticles onto a substrate is controlled using "click" chemistry under an external magnetic field. Co‐aligned single nanoparticle chains separated by regular distances can be obtained by this strategy. The intrinsic high uniaxial anisotropy results in a strong enhancement of magnetic collective properties in comparison to 2D monolayers or isolated nanoparticles. In contrast to the intensively studied bundle chains of nanoparticles, the finely tuned chain structure reported here allows evidencing a first order intrachain dipolar interaction and a second order interchain magnetic coupling. This study offers new insights into the collective magnetic properties of highly anisotropic particulate assemblies which have been investigated by combining superconducting quantum interference device magnetometry, magnetic force microscopy, and ferromagnetic resonance. Abstract : Anisotropic uniaxial assemblies of substrate‐bound iron oxide nanoparticles are prepared by "click" chemistry under an external magnetic field. The resulting nanoparticle chains are co‐aligned with regular spacing and possess enhanced magnetic collective properties. The novel, highly ordered assembly allows evidencing a first order intrachain dipolar interaction, combined with a second order interchain magnetic coupling.